Association between the body roundness index and female infertility: a cross-sectional study from NHANES - Liu, Ming; Zhang, Yifang; Liu, Jian (Frontiers in Endocrinology, 2025)
BackgroundInfertility is strongly associated with obesity. The body roundness index (BRI) is a more accurate assessment of visceral fat content than the body mass index (BMI). However, current evidence on the association between visceral fat accumulation and infertility remains insufficient and controversial. Therefore, we utilized the 2017-2020 National Health and Nutrition Examination Survey (NHANES) database to explore the correlation between BRI and infertility.MethodsWe used multiple logistic regression, smoothed curve fitting, subgroup analyses, and interaction tests to investigate the potential association between BRI and infertility. Additionally, we assessed the ability of BRI and BMI to predict infertility risk using receiver operating curve (ROC) analysis and calculate the area under the curve (AUC),sensitivity, and specificity.ResultsIn the study, 1463 women aged 20 to 45 participated, and 172 of them were found to be infertile. After adjusting for all factors except body measurements, the findings indicated that for each one-unit increase in BRI, there was a 19% increase in the risk of infertility (OR = 1.19, 95% CI 1.05, 1.34). The analysis also revealed a positive nonlinear relationship between BRI and infertility. Furthermore, based on the ROC curves, it was observed that BRI was a more reliable predictor of infertility risk compared to BMI (BRI AUC = 0.5773, BMI AUC = 0.5681).ConclusionThis study demonstrated a positive association between higher BRI values and infertility among adult women in the United States and showed a stronger association than BMI.